CARCINOMA MAMÁRIO EM CÃO MACHO - Henz, Nadine Cristiane; Lusa, Tatiane; Schneider, Marla; Benetti, Juliana Eliza; de Lima, Jéssica Line Farias (Anais de Medicina Veterinária; v. 2 n. 1 (2022): 2022/2, 2022)
.